Pelatihan Pendidik Sebaya Tentang Status Gizi dan Masalah Kesehatan Reproduksi Remaja di SMA N 1 Donorojo Jepara - Veftisia, Vistra; Dian A, Luvi; Kristiningrum, Wahyu (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
Adolescents are often classified as a group that is always healthy away from risk factors for illness, but many health problems suffered by adolescents due to behavioral factors that can actually be prevented. Adolescents are faced with complex problems related to physical, psychological and emotional changes that cause them to experience health problems. Some of the health problems that often occur are nutrition and reproductive health. Prevention can be done if students make early detection of nutritional problems and adolescent reproductive health problems with the support of the environment both at home and at school. The obstacle that often occurs in schools is the large comparison between the number of health service providers and the number of students in the school. The role of adolescent health cadres is to help adolescents be more comfortable discussing issues of nutrition and adolescent reproductive health, health education and strengthening about early childhood development and social media divided into 2 stages of implementation. Data collection instruments in the form of questionnaires. The activity was carried out at SMA N 1Donorojo Jepara with the method of providing training to students who would be used as peer educators about nutritional status and adolescent reproductive health problems with the small group method of discussion in the delivery of material, which was divided into 2 stages of implementation, namely training and evaluation. The data collection instrument is in the form of a questionnaire. It was found that there was an increase in the knowledge of adolescent health cadres after the training. This peer educator training becomes a means of providing information which can later be continued to peers so that it can increase knowledge of adolescents in high school about nutritional status and adolescent reproductive health problems.ABSTRAKRemaja sering digolongkan sebagai kelompok yang selalu sehat jauh dari faktor resiko sakit, namun banyak masalah kesehatan yang diderita oleh remaja karena faktor perilaku yang sebenarnya bisa dicegah. Remaja dihadapkan pada permasalahan yang komplek terkait dengan perubahan fisik, psikis dan emosi yang menyebabkan remaja mengalami masalah kesehatan. Beberapa masalah kesehatan yang sering terjadi adalah gizi dan kesehatan reproduksi. Pencegahan dapat dilakukan jika siswa melakukan deteksi dini masalah gizi dan masalah kesehatan reproduksi remaja dengan adanya dukungan dari lingkungan baik dirumah dan disekolah. Kendala yang sering terjadi di sekolah adalah perbandingan yang cukup besar antara jumlah pelaksana pelayanan kesehatan dengan jumlah siswa di sekolah. Peran kader kesehatan remaja untuk membantu remaja lebih nyaman berdiskusi tentang masalah gizi dan kesehatan reproduksi remaja.Pelaksanan kegiatan dilaksnakan di SMA N 1Donorojo Jepara dengan metode pelaksanaan pemberian melatih siwa yang akan dijadikan pendidik sebaya tentang stataus gisi dan masalah Kesehatan reproduksi remaja dengan metode small group dicussiun dalam penymapain materi, yang terbagi menjadi 2 tahap pelaksanaan yaitu pelatihan dan evaluasi. Instrumen pengumpulan data berupa kuesioner. Didapatkan ada peningkatan pengetahuan kader kesehatan remaja setelah dilakukan pelatihan. pelatihan pendidik sebaya ini menjadi sarana pemberian informasi yang nantinya bisa dilanjutkan kepada teman sebaya sehingga dapat meningkatkan pengetahuan pada remaja di SMA tentang stataus gisi dan masalah Kesehatan reproduksi remaja .